Knowledge of Teenagers From the Bilingual Experimental High School of Grecia About Teratogens and Its Effect On Human Embryos - Quirós Vargas, Elsie (2017)
This paper analyzes the chemical substances known as teratogens, their consequences in the human fetus, and the knowledge level of 16 and 17 year-old students from the Bilingual High School of Grecia about the aforementioned agents. Alcohol, tobacco, and street drugs are excluded from this work due to the abundant exposure against human intake of these during pregnancy. The purpose was to demonstrate the cohort’s understanding level about the topic, outline which chemicals are dangerous, apply a questionnaire to determine how much they know, and identify the daily-use products which contain these elements. In conclusion, teratogenic materials are present in a wide variety of artificial goods. Exposure to these may harm the neonate in formation. The majority of youngsters who participated do not know what a teratogen is, its implications in pregnancy, how to recognize it, and they live in areas that could be affected by teratogenic ingredients.